Adubação NPK do Tabaco (Nicotiana tabacum) num solo da Zona da Mata, Minas Gerais: III - composição mineral das folhas - E O Begazo, José Carlos; Ferreira de Novais , Roberto; Dias Nogueira, Francisco (Revista Ceres, 2025)
Using the tabacco variety ‘Chinés n. 1', a variety grown for its yield of cigar wrapper, the effects of 10 NPK treatments were tested under field conditions at Rio Pomba, Minas Gerais.